2014
DOI: 10.17221/7242-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Determination of haematological and biochemical parameters of Przewalski horses (Equus przewalski) kept by the Prague Zoo

Abstract: ABSTRACT:The objective of this study was to determine ranges of haematological and biochemical parameters of Przewalski horses (Equus przewalski) kept in the Czech Republic, to compare the results with data reported for the same species as well as for domestic horses (Equus caballus), and to evaluate differences between both genders and age groups. Stallions showed significantly higher counts of red blood cells and bands, higher levels of total bilirubin and magnesium, and a higher activity of GGT. Higher conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
1
8
4
1
Order By: Relevance
“…As to the complete WBC count in the examined mares, there were certain differences. Contrary to the results obtained by other authors (Da Costa et al 2003, Aoki and Ishi 2012, Mariella et al 2014, Tomenendalova et al 2014Meliani et al 2015, our study revealed that before the parturition, WBC count was rather high with and amounted to 11.01 ±3.62 (x103/mL) and 10.01 ± 2.03 (x103/mL) for the mares from group I and group II, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…As to the complete WBC count in the examined mares, there were certain differences. Contrary to the results obtained by other authors (Da Costa et al 2003, Aoki and Ishi 2012, Mariella et al 2014, Tomenendalova et al 2014Meliani et al 2015, our study revealed that before the parturition, WBC count was rather high with and amounted to 11.01 ±3.62 (x103/mL) and 10.01 ± 2.03 (x103/mL) for the mares from group I and group II, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the physiological parameters (Table 2), the level of hemoglobin was higher than the other parameters, such as lymphocytes and total red and white blood cells. Studies conducted on the Przewalski horse also reported a higher hemoglobin value and a lower lymphocyte value [13].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted to determine baseline values for haematology in working donkeys (Etana et al 2011 ), there were significant variations in total leucocyte, MCV and neutrophil counts between sexes. Male Przewalski horses were characterized by significantly higher erythrocyte count and immature neutrophilic granulocytes than female Przewalski horses (Tomenenendalova et al 2014 ). In the experiment conducted by Tomenenendalova et al ( 2014 ), stallions were also observed to have a relatively higher haemoglobin concentration and leucocyte and monocyte counts than mares but without significant significance.…”
Section: The Role Of Sex On Haematology Of Donkeysmentioning
confidence: 99%
“…Male Przewalski horses were characterized by significantly higher erythrocyte count and immature neutrophilic granulocytes than female Przewalski horses (Tomenenendalova et al 2014 ). In the experiment conducted by Tomenenendalova et al ( 2014 ), stallions were also observed to have a relatively higher haemoglobin concentration and leucocyte and monocyte counts than mares but without significant significance. The PCV and haemoglobin concentration are lower in mares than in working horses with low body condition scores (Pritchard et al 2009 ).…”
Section: The Role Of Sex On Haematology Of Donkeysmentioning
confidence: 99%